Boost your Children’s Appetite with Homoeopathy – Holistic Approach (Homoeopathy for All, 2024)
Loss of appetite is not feeling  hungry or having a desire to eat.  Child may experience a loss or  decrease in appetite during times  of slower growth or for a variety of  other reasons. Most of the time, an  occasional loss of appetite is nothing  to worry about. If child appears to  be losing weight or talking about  wanting to be thinner, then special  care should given for these child’s.  These can be signs of a physical  illness, or anorexia, a condition  that often requires both physical  treatment and counseling to resolve.  Parents can try several approaches to  help their child regain his appetite.
Keywords: Ormand; winter; Children’s